-6-2(-9x-8)=-3

Simple and best practice solution for -6-2(-9x-8)=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6-2(-9x-8)=-3 equation:


Simplifying
-6 + -2(-9x + -8) = -3

Reorder the terms:
-6 + -2(-8 + -9x) = -3
-6 + (-8 * -2 + -9x * -2) = -3
-6 + (16 + 18x) = -3

Combine like terms: -6 + 16 = 10
10 + 18x = -3

Solving
10 + 18x = -3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + -10 + 18x = -3 + -10

Combine like terms: 10 + -10 = 0
0 + 18x = -3 + -10
18x = -3 + -10

Combine like terms: -3 + -10 = -13
18x = -13

Divide each side by '18'.
x = -0.7222222222

Simplifying
x = -0.7222222222

See similar equations:

| s=q+3/x | | .40c+4-.20c=-9 | | -23=-t | | b-4c+3a-c-9b-4a=0 | | 5(6x-5)+51=-6(x-7)+18x+2 | | -8x-9+5x=-9x+3 | | x+3=5x+2 | | 4.9t^2+2.14t+42=0 | | 5F-9C=120 | | 3/2*16*1/2 | | 7/2*16*-1/2 | | .5x-2.3=0.7 | | 3x+7x+4=2x-6 | | -21.15=m-6.33-6.7m | | 15/2*64*-1/2 | | -8a-b-(-6c)-2a-b-5c=0 | | x-3/10-8=3x+2 | | 6-2x+7-3x=12 | | 2*6*w+2*w*8+2*6*8=208 | | 9x-7=9(x-5) | | 15/2((64)-1/2) | | -2c=pm^2-n | | -(x+2)=-18-x | | X-5/3=5/4 | | x/5=-23 | | 1/2(0.75-0.25) | | -8x+16=-3x-4 | | 3(43)-8+43+2(98.5)-17=180 | | 7d-12+3=18 | | 32-8k=-6+6(-7-8k) | | 6r^2+13r-63=0 | | 1.00/2.00(0.75-0.25) |

Equations solver categories